2015
DOI: 10.1371/journal.pone.0141649
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Transient Elastography, Acoustic Radiation Force Impulse Imaging (ARFI), and Enhanced Liver Function (ELF) Score for Detection of Fibrosis in Morbidly Obese Patients

Abstract: BackgroundLiver fibrosis induced by non-alcoholic fatty liver disease causes peri-interventional complications in morbidly obese patients. We determined the performance of transient elastography (TE), acoustic radiation force impulse (ARFI) imaging, and enhanced liver fibrosis (ELF) score for fibrosis detection in bariatric patients.Patients and Methods41 patients (median BMI 47 kg/m2) underwent 14-day low-energy diets to improve conditions prior to bariatric surgery (day 0). TE (M and XL probe), ARFI, and ELF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 35 publications
(58 reference statements)
1
47
1
1
Order By: Relevance
“…Karlas et al . reported that ARFI overestimated the severity of liver fibrosis in the most obese patients . However, Nishikawa et al .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Karlas et al . reported that ARFI overestimated the severity of liver fibrosis in the most obese patients . However, Nishikawa et al .…”
Section: Discussionmentioning
confidence: 94%
“…In obese patients, measurement failures have occurred using the FibroScan (Echosens, Paris, France) M probe, which has standard specifications, and the usefulness of the XL probe has been reported . Recently, measurement failures using ARFI were shown to occur in obese patients . Several reports have examined the reliability of LSM methods using US in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in agreement with previous studies in less obese patients that have shown that the skin-to-liver capsule distance plays an important role in failure of liver stiffness measurement. [17,[28][29][30][31] From these data, the M probe is currently recommended for patients with a skin-capsular distance of less than 25 mm, whereas for all other patients, the XL probe should be used. [17] In our cohort, we could also demonstrate that patients with reliable Fibroscan V R measurements had a significantly lower mean distance between skin and liver capsule compared to those patients with not valid and not successful measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Nine of these recruited patients from obese‐only cohorts. Five bariatric surgical studies reported liver biopsies on all bariatric surgical patients . In all studies, one or two dedicated pathologists scored all liver biopsies.…”
Section: Resultsmentioning
confidence: 99%